2021
DOI: 10.1007/s40203-021-00093-y
|View full text |Cite
|
Sign up to set email alerts
|

In silico and in vitro screening of licensed antimalarial drugs for repurposing as inhibitors of hepatitis E virus

Abstract: Hepatitis E virus (HEV) infection is emerging in Cameroon and represents one of the most common causes of acute hepatitis and jaundice. Moreover, earlier reports showed evidence of falciparum malaria/HEVcoexistence. Although the Sofosbuvir/Ribavirin combination was recently proposed in the treatment of HEV-infected patients, no specific antiviral drug has been approved so far, thereby urging the search for new therapies. Fortunately, drug repurposing offers a good alternative to this end. In this study, we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…To assess whether ART might interact with the HEV helicase and RdRp proteins, which are the key enzymes involved in HEV RNA replication, we used a computational approach. Galani et al [ 38 ] have reported that artemisinin, the parent molecule of ART, has low binding affinity to HEV RdRp; hence, we focused on HEV helicase. As there was no crystal structure of HEV helicase in the PDB database, the 3-D structure was predicted using tomato mosaic virus (ToMV) helicase, which has 32% sequence identity, as a template.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To assess whether ART might interact with the HEV helicase and RdRp proteins, which are the key enzymes involved in HEV RNA replication, we used a computational approach. Galani et al [ 38 ] have reported that artemisinin, the parent molecule of ART, has low binding affinity to HEV RdRp; hence, we focused on HEV helicase. As there was no crystal structure of HEV helicase in the PDB database, the 3-D structure was predicted using tomato mosaic virus (ToMV) helicase, which has 32% sequence identity, as a template.…”
Section: Resultsmentioning
confidence: 99%
“…It was documented previously that anti-malarial drugs such as amodiaquine, lumefantrine, and pyrimethamine have potential antiviral activity against HEV-3. As docking of artemisinin, an analog of ART, with different HEV proteins showed low scores with HEV protease and RdRp, it was not investigated further [ 38 ]. Since our experiments showed effective inhibition of HEV-1 with ART, comparable to that observed with ribavirin, we performed a docking simulation with HEV helicase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The active site residues (i.e., Arg366, Arg399, Gln420, Gln421, Asp444, and Gln446) were selected on the basis of previously reported studies [ 22 ]. A total 100 antimicrobial tetrapeptides were docked to the receptor protein (capsid protein) of HEV.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, Galani et al [ 22 ] investigated eight licensed antimalarial drugs and two anti-hepatitis C virus agents (i.e., sofosbuvir and ribavirin) as inhibitors of five different target proteins of the HEV genome. These ten compounds were docked counter to RdRp, zinc-binding non-structural protein, capsid protein, cryoEM structure of HEV VLP, and the E2s domain of HEV genome.…”
Section: Discussionmentioning
confidence: 99%